A state-space approach to stand growth modelling of European beech - Nord-Larsen, Thomas; Johannsen, Vivian K. (Annals of forest science., 2007)
Static models of forest growth, such as yield tables or cumulative growth functions, generally fail to recognize that forest stands are dynamic systems, subject to changes in growth dynamics due to silvicultural interventions or natural dynamics. Based on experimental data, covering a wide range of initial spacings and thinning practises, we developed a dynamic stand growth model of European beech in Denmark. The model entailed three equations for predicting dominant height growth, basal area growth, and mortality. The signs of the parameter estimates generally corroborated the anticipated growth paths of dominant height and basal area. Although statistical tests indicated significant systematic deviations between observed and predicted values, the deviations were small and of little practical importance. Cross validation procedures indicated that the model may be applied across a wide range of growth conditions and thinning practises without significant loss of precision.